2004
DOI: 10.1097/01.ta.0000085852.55853.3a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the LT-α (+250 G/A) Polymorphism on Markers of Inflammation and Clinical Outcome in Critically Ill Patients

Abstract: There was no correlation between the biallelic LT-alpha (+250 G/A) polymorphism and the outcome of critically ill patients. Genotyping this locus does not seem to be useful in predicting sepsis outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…In the LTA (+250 G/A) analysis no association was observed corroborating the findings of Rauchschwalbe et al (2004) and Gong et al (2005). Furthermore, Schueller et al (2006) suggested the likelihood that this polymorphism does not serve as a prognostic marker for elevated sepsis risk in preterm infants.…”
Section: Discussionsupporting
confidence: 73%
“…In the LTA (+250 G/A) analysis no association was observed corroborating the findings of Rauchschwalbe et al (2004) and Gong et al (2005). Furthermore, Schueller et al (2006) suggested the likelihood that this polymorphism does not serve as a prognostic marker for elevated sepsis risk in preterm infants.…”
Section: Discussionsupporting
confidence: 73%
“…This association was also found by other investigators [28], but others were unable to demonstrate an association between this polymorphism and outcome in patients with sepsis [11]. Similar contradictory findings have been reported in the case of TNF-β ( Nco I polymorphism); mortality in severe sepsis was higher in TNFB2 (AA) individuals [29,30], although other investigations found no such association [31]. A recent study enrolling 213 patients with severe sepsis [32] found no association between these polymorphisms and mortality.…”
Section: Discussionsupporting
confidence: 71%
“…Levels and the biological activity of many of the inflammatory markers in the body are known to be under significant genetic control. The same has been shown in the case of CRP, IL‐12, and Neo [16–18]. Polymorphisms in the genes controlling these inflammatory markers were not studied by us and could certainly have confounded our study results.…”
Section: Discussionsupporting
confidence: 60%